On the influence of micro- and macro-cristalline paraffins on the physical and rheological properties of crude oil and organic solvents - de Oliveira, Marcia; Vieira, Lenise; Miranda, Luise; Miranda, Daniele; Marques, Luiz C. C. (Publishing House of Lviv Polytechnic National University, 2016)
The influence of micro- and macro-crystalline paraffins on the properties of crude oil and organic solvents was investigated. Micro-cristalline paraffins promote the most pronounced changes in the investigated physical and rheological properties of all tested solutions. The concentration of branched-alkanes in paraffins is the pivotal parameter that promotes these changes. Досліджено вплив мікро- і макрокристалічних парафінів на властивості сирої нафти і органічних розчинників. Показано, що мікрокристалічні парафіни мають найбільший вплив на фізичні та реологічні властивості досліджуваних компонентів. Встановлено, що концентрація розгалужених алканів в парафінах є ключовим параметром, який зумовлює зміни властивостей.
Про вплив мікро- і макрокристалічних парафінів на фізичні та реологічні властивості сирої нафти і органічних розчинників
Keywords: flow of waxy crude; micro- and macroparaffins; rheological properties; wax appearance temperature; yield stress; парафіниста нафта; мікро- і макропарафіни; реологічні властивості; температура появлення парафіну; межа текучості